Candida Infections and Their Prevention. (4th November 2013) - Kabir, M. Anaul; Ahmad, Zulfiqar
Abstract : Infections caused by Candida species have been increased dramatically worldwide due to the increase in immunocompromised patients. For the prevention and cure of candidiasis, several strategies have been adopted at clinical level. Candida infected patients are commonly treated with a variety of antifungal drugs such as fluconazole, amphotericin B, nystatin, and flucytosine. Moreover, early detection and speciation of the fungal agents will play a crucial role for administering appropriate drugs for antifungal therapy. Many modern technologies like MALDI-TOF-MS, real-time PCR, and DNA microarray are being applied for accurate and fast detection of the strains. However, during prolonged use of these drugs, many fungal pathogens become resistant and antifungal therapy suffers. In this regard, combination of two or more antifungal drugs is thought to be an alternative to counter the rising drug resistance. Also, many inhibitors of efflux pumps have been designed and tested in different models to effectively treat candidiasis. However, most of the synthetic drugs have side effects and biomedicines like antibodies and polysaccharide-peptide conjugates could be better alternatives and safe options to prevent and cure the diseases. Furthermore, availability of genome sequences of Candida    albicans and other non- albicans strains has made it feasible to analyze the genes for their roles in adherence, penetration, and establishment of diseases. Understanding the biology of Candida species by applying different modern and advanced technology will definitely help us in preventing and curing the diseases caused by fungal pathogens.